Some aspects of combating terrorism in Great Britain (International relations and international law Journal, 2018)
Now terrorism became the real threat not only for the certain states, but also for all world community.Great Britain belongs to those countries in which rather successfully fight against extremism and havecertain practices according to prevention of extremist manifestations. In article the conclusion is drawnthat the principles of the organization of fight by extremism, and first of all her preventive character andbroad cooperation with the population are the reason of successful «prevention of youth extremism inGreat Britain». At acquaintance with the documents concerning activities of police of the United Kingdomfor prevention and suppression of extremist activity and when viewing a number of the websitesbelonging to offices of police of Great Britain, the fight against youth extremism having generally preventivecharacter is often conducted not so much globally how many «pointswise» and «precisely». Howeverwhen developing practical recommendations in the sphere of communication counteraction to terrorismin is necessary to consider both positive, and negative experience, therefore studying of various directionsof anti-terrorist activity of the countries of the West is represented relevant and important.Key words: Great Britain, terrorism, extremism, struggle, IRA, MI5, international, national and religiousminorities, police.